Pengaruh Substrat yang Berbeda Terhadap Daya Tetas Telur Ikan Cupang (Betta Splendens) - Yenni Afrida; Azwar Thaib; Nurhayati Nurhayati (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Betta fish (Betta splendens) is one type of freshwater ornamental fish that has the potential to be cultivated because it has high economic value. This study aims to determine the appropriate substrate for hatchability of betta fish eggs. This study uses a non factorial Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatments were control (treatment A), dried ketapang leaf substrate (treatment B), dried coconut leaf substrate (treatment C) and dried banana leaf substrate (D). The container used is a jar with a volume of 10 l and filled with water as much as 5 l, dense stocking of betta fish eggs as much as 50 grains / liter. Observation parameters included hatching time, hatchability and survival rate of betta fish larvae. The results of this study were analyzed using the one way Anova test. The results showed that the use of different substrates significantly affected the egg hatchability and survival rate of betta fish (P <0.05). The best results were found in treatment B giving ketapang leaves with an egg hatchability value of 89% and survival rate of betta fish larvae of 80%..